From Laboratory Know-how to Field Show-how in Timber Engineering - Masani, N. J. (Indian Forester, 1968)
Great significance is being attached to the applied research programmes of our National Research Laboratories and Research Institutions so that the laboratory ’know-hows’ may be of immediate value in the promotion of developmental activities and stabilization of country’s economy. This paper narrates the usefulness of modern Timber Engineering research projects at the Forest Research Institute. It cites the illustrative examples of new techniques and developments in the workshop laboratory and their equivalent demonstration and economical application in the construction field. The following specific problems based on modern Timber Engineering technique have been discussed:- (a) Adoption of secondary species for structural purposes. (b) Use of short length small dimensioned timbers in constructional works. (c) Effective and economical jointing devices for timber structures. (d) New trends in timber structures. (e) Anti-termite gadgets by constructional methods. As such the main aim of our research studies is to extend the knowledge gained in the design offices, research laboratories and workshops to the Engineers, Architects, Builders and Foresters in the field for adoption in their extension works and achieving the much-sought-for economy in construction costs and at the same time conserve the building materials. The case for rational utilization of timber as a structural material in the present and future construction programmes have been presented by giving ’know-hows’ ’show-hows’ and the economy available in the various aspects of modern timber engineering practices.